Translation, cross-cultural adaptation, and validation of the HCT frailty scale for hematopoietic stem cell transplant candidates: an observational study - Luz Lorca; Barbara Puga Larrain; Ivana Leao Ribeiro; Ivana Gonzalez Valdivia; Angelia Fernández Hermoso; Francisca Bass Maturana; Francisco Canelo Lazcano (Hematology, Transfusion and Cell Therapy)
Introduction: Hematopoietic stem cell transplantation (HSCT) is a treatment option for patients with hematologic malignancies. The aim of this study is to validate the Hematopoietic Cell Transplantation Frailty Scale in a Chilean population. Methods: This was a cross-sectional scale validation study. The sample consisted of patients with various hematologic malignancies who were transplantation candidates. The study had two stages: (1) translation (forward and backward) and (2) psychometric analysis, including face validity, test-retest reliability, and content validity. Descriptive analyses included mean, standard deviation, and the 95 % confidence interval. Reliability was assessed with Spearman's correlation, and content validity used Kendall's W test. Results: Fifty-four patients (53.7 % women) were included, with multiple myeloma being the most frequent diagnosis (33.3 %). Positive and strong correlations were identified (Spearman's Rho [ρ]: 1.0; p-value <0.001) for all items on the scale. Regarding content validity, there was agreement among evaluators for the categories of relevance and coherence (p-value <0.01; Kendall's W range: 0.13–0.17) but not for “clarity” (p-value = 0.11; Kendall's W: 0.07). Some terms in the content were adjusted without affecting the overall structure of the scale. In the retest analysis, descriptive values were similar to the initial test. Conclusion: The Spanish version of the Hematopoietic Cell Transplantation Frailty Scale for Chile is conceptually and linguistically equivalent to the original instrument. Additionally, it demonstrated adequate psychometric properties in terms of validity and reliability.